THU0088 Fetuin-A and Its Association with Disease Activity in Psoriatic Arthritis. (10th June 2014) - Ozturk, S.; Keser, M.; Kozaci, D.; Cetin, P.; Gunay, N.; Onen, F.; Akkoc, N.; Sari, I.
Abstract : Background: Increased risk of cardiovascular morbidity and mortality has been reported in psoriatic arthritis (PsA), a member of a spondyloarthropathy. Fetuin-A is a novel biomarker related with vascular calcification and atherosclerosis. In recent years there is a considerable interest regarding fetuin-A and atherosclerosis. In this respect it has been studied in some rheumatic disease including rheumatoid arthritis. However, available data regarding the association of fetuin-A and inflammatory rheumatic diseases is still limited. Objectives: In this study we aimed to investigate the association between fetuin-A, disease activity and PsA. Methods: 97 non-diabetic PsA patients who fulfilled the CASPAR criteria and 57 age and sex matched healthy controls were included in the study. Disease activity was assessed by using Composite Psoriatic Disease Activity Index (CPDAI). Patients were also evaluated with BASFI, BASDAI, DAS28-CRP, HAQ. PASI scores were calculated. Serum lipids, hsCRP, ESR, and fetuin-A were studied. Results: There were 97 PsA patients (48 [25-65] years, 32M/65F) and 57 healthy subjects (43 [31-57] years, 24M/33F). Disease duration of the PsA patients was 4 (0-43) years. Age, sex distributions, anthropometric measures such as body mass index were similar between the groups. Biochemical parameters such as fasting glucose, lipids (triglyceride, total, LDL and HDL), creatinine clearance were not different PsA patients and controls. On the other hand hs-CRP and ESR were significantly higher in the patients' group. Fetuin-A concentrations were significantly lower in the patients than in controls (Table 1, P<0.001). When the PsA group was divided into peripheric (n=14), axial (n=52) and both peripheric and axial subtypes (n=31) fetuin A remained significantly lower in the each PsA group compared to controls (peripheric: 1122 [571-1493], axial 1172 [456-2017] and both peripheric and axial subtypes 1113 [486-1580] vs. controls 1442 [63-1896]; P<0.05). On the other hand, there were no differences between the PsA groups regarding fetuin A. There were significant correlations (P<0.05) between fetuin-A concentrations and CPDAI, PASI, hs-CRP and ESR (-0.26, -0.25, -0.3, and -0.26 respectively). However, fetuin-A did not show correlations with BASFI, BASDAI, HAQ and DAS28-CRP. Conclusions: Fetuin-A levels were significantly down-regulated in PsA patients regardless of the involvement type. Correlations between fetuin-A, acute phase proteins and disease activity indices suggest that inflammation driven mechanisms are reponsible from this condition. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4473